The Effect of Inflation, Interest Rates and World Oil Prices on Gold Prices in Indonesia with the US Dollar Exchange Rate as an Intermediary Variable - Kalsum, Ummi; Hidayat, Randy; Oktaviani, Sheila (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
This study aims to determine the effect of inflation, interest rates, and world oil prices on fluctuations in gold prices in Indonesia with the US Dollar exchange rate as an intermediary variable. This research is a type of explanatory research with a quantitative approach. The data used are monthly time series data for 2014 - 2019 with a sample of 72 samples. Hypothesis testing in this study uses path analysis, is a development technique of multiple linear regression. This technique is used to test the amount of contribution shown by the path coefficient on each path diagram of the causal relationship between cariables X1, X2, and X3 on and its impact on Z. The results of this study indicate that the effect of inflation, interest rates and worl oil prices on exchange rates individually has very little effect. The effect of inflation, interest rates, world oil prices and the exchange rate on gold prices individually shows a negative value for inflation and interest rates means that the effect is small, while for the world oil price and the dollar exchange rates shows a positive value which means that it has a large effect on the price of gold. The effect of inflation, interest rates and world oil prices on gold prices through the exchange rate, all variable show a negative value, this indicates that the effect is very small.